Spatial behavior reflects the mental disorder in OCD patients with and without comorbid schizophrenia. (11th July 2013) - Gershoni, Anat; Hermesh, Haggai; Fineberg, Naomi A.; Eilam, David
<x content-type="archive" xml:space="preserve">Abstract</x> Objective Resolving the entangled nosological dilemma of whether obsessive-compulsive disorder (OCD) with and without schizophrenia (schizo-OCD and OCD, respectively) are two independent entities or whether schizo-OCD is a combined product of its parent disorders. Methods Studying motor activity in OCD and in schizo-OCD patients. Performance of the patients was compared with the performance of the same motor task by a matching control individual. Results Behavior in both schizo-OCD and OCD patients differed from controls in the excessive repetition and addition of acts, thus validating an identical OC facet. However, there was a significant difference in spatial behavior. Schizo-OCD patients traveled over a greater area with less focused activity as typical to schizophrenia patients and in contrast to OCD patients, who were more focused and traveled less in a confined area. While schizo-OCD and OCD patients share most of the OC ritualistic attributes, they differ in the greater spread of activity in schizo-OCD, which is related to schizophrenia disorder. Discussion It is suggested that the finding on difference in spatial behavior is a reflection of the mental differences between OCD and schizophrenia. In other words, this could be an overt and observable manifestation of the mental state, and therefore may facilitate the nosology of OC spectrum disorders and OCD. Conclusion It seems as if both the OCD patients' focus on specific thoughts, and the contrasting wandering thoughts of schizophrenia patients, are reflected in the focused activity of the former and wandering from one place to the next of the latter.